2022
DOI: 10.3389/fchem.2022.1003163
|View full text |Cite
|
Sign up to set email alerts
|

Energetic electron irradiations of amorphous and crystalline sulphur-bearing astrochemical ices

Abstract: Laboratory experiments have confirmed that the radiolytic decay rate of astrochemical ice analogues is dependent upon the solid phase of the target ice, with some crystalline molecular ices being more radio-resistant than their amorphous counterparts. The degree of radio-resistance exhibited by crystalline ice phases is dependent upon the nature, strength, and extent of the intermolecular interactions that characterise their solid structure. For example, it has been shown that crystalline CH3OH decays at a sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The (so far) nondetection of solid-phase H 2 S in interstellar clouds thus poses a question regarding the fate of H 2 S in interstellar icy mantles. One likely explanation for its absence in observations is that solid-phase H 2 S is effectively destroyed by, for instance, energetic processing, which is known to result in solid-phase sulfur chemistry (e.g., Moore et al 2007;Garozzo et al 2010;Jiménez-Escobar & Muñoz Caro 2011;Jiménez-Escobar et al 2014;Chen et al 2015;Shingledecker et al 2020;Cazaux et al 2022;Mifsud et al 2022). In fact, the photochemistry of H 2 S induced by UV photons has been suggested as a potential sulfur sink, as it has been shown to produce allotropic forms of S (S n ) that are largely refractory (especially for n > 4).…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The (so far) nondetection of solid-phase H 2 S in interstellar clouds thus poses a question regarding the fate of H 2 S in interstellar icy mantles. One likely explanation for its absence in observations is that solid-phase H 2 S is effectively destroyed by, for instance, energetic processing, which is known to result in solid-phase sulfur chemistry (e.g., Moore et al 2007;Garozzo et al 2010;Jiménez-Escobar & Muñoz Caro 2011;Jiménez-Escobar et al 2014;Chen et al 2015;Shingledecker et al 2020;Cazaux et al 2022;Mifsud et al 2022). In fact, the photochemistry of H 2 S induced by UV photons has been suggested as a potential sulfur sink, as it has been shown to produce allotropic forms of S (S n ) that are largely refractory (especially for n > 4).…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…by quantum tunneling through an effective barrier of ∼1500 K (Lamberts & Kästner 2017). The HS radical can subsequently be hydrogenated to reform H 2 S. Alternatively, H 2 S can also be energetically processed to form species such as H 2 S 2 and a wide range of S allotropes (Moore et al 2007;Garozzo et al 2010;Jiménez-Escobar & Muñoz Caro 2011;Jiménez-Escobar et al 2014;Chen et al 2015;Shingledecker et al 2020;Cazaux et al 2022;Mifsud et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur allotropes have been proposed as an important sulfur reservoir in molecular clouds 18 , formed, for example, upon UV irradiation of H 2 S ices 19 , or electron irradiation of H 2 S and SO 2 ices 20 . In the latter laboratory study, an apparent depletion of accountable sulfur budget was observed, attributed to the possible formation of sulfur allotropes.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Indeed, previous experimental work has suggested that the irradiative processing of SO 2 ice using 1.5 keV electrons results in a relatively facile conversion to infrared-inactive molecular forms of sulphur. 13 The detection of SO 2 on various Solar System bodies has also proven to be somewhat contentious, due to these observations primarily relying on ultraviolet-visible spectroscopy, which is more ambiguous than infrared spectroscopy in categorically assigning absorption features to particular molecular species. For example, Hendrix et al 14 suggested that the observed ultraviolet-visible reflectance spectra of the dwarf planet Ceres between 320-400 nm could be approximated fairly well by laboratory spectra of phyllosilicate minerals (such as montmorillonite) intermixed with solid SO 2 and allotropic forms of elemental sulphur.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Indeed, previous experimental work has suggested that the irradiative processing of SO 2 ice using 1.5 keV electrons results in a relatively facile conversion to infrared-inactive molecular forms of sulphur. 13…”
Section: Introductionmentioning
confidence: 99%